2018
DOI: 10.5604/01.3001.0012.8275
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes after Scaphoid Excision and Midcarpal Arthrodesis for SNAC and SLAC Wrist Arthritis

Abstract: Background. Persistent, long-lasting pseudoarthrosis of the scaphoid or scapholunate dissociation results in arthrosis of the radio-scaphoid joint termed scaphoid non-union advanced collapse (SNAC) or scapholunate advanced collapse (SLAC), which causes pain, reduction in wrist movements and weakness of the hand grip. Scaphoid resection followed by „four-corner” midcarpal arthrodesis is a recognized treatment for this condition. Material and methods. The study evaluated the results of treatment of 27 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The triquetrum excision group ( n = 75, 4 studies 8 11 14 15 ) showed improvement in the differences between pre-and postoperative F–E arc motion compared with the 4CF group ( n = 261, 10 studies 21 23 24 28 31 33 34 35 38 40 ) of 5.8 degrees versus −11 degrees ( Table 3 ). Similarly, the triquetrum excision group ( n = 62, three studies 8 14 15 ) showed improvement in the R–U arc motion compared with the 4CF group ( n = 251, nine studies 21 23 28 31 33 34 35 38 40 ) with a difference of 5 degrees versus −3 degrees ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The triquetrum excision group ( n = 75, 4 studies 8 11 14 15 ) showed improvement in the differences between pre-and postoperative F–E arc motion compared with the 4CF group ( n = 261, 10 studies 21 23 24 28 31 33 34 35 38 40 ) of 5.8 degrees versus −11 degrees ( Table 3 ). Similarly, the triquetrum excision group ( n = 62, three studies 8 14 15 ) showed improvement in the R–U arc motion compared with the 4CF group ( n = 251, nine studies 21 23 28 31 33 34 35 38 40 ) with a difference of 5 degrees versus −3 degrees ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…1 . There were 21 4CF articles 9 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 and 11 2/3CF articles 5 8 9 11 14 15 16 17 18 19 41 included for analysis ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In these conditions, surgical procedures are planned based on the status of the joint preservation from the disease. For instance, if the lunate fossa and capitate cartilage are spared, proximal row carpectomy is an acceptable choice in radiocarpal arthritis or lunate avascular necrosis cases [9][10][11].…”
Section: Bones and Jointsmentioning
confidence: 99%